Defoliation and bark harvesting affect life‐history traits of a tropical tree. (5th August 2013) - Gaoue, Orou G.; Horvitz, Carol C.; Ticktin, Tamara; Steiner, Ulrich K.; Tuljapurkar, Shripad
Summary: Selectively harvesting whole individuals in managed populations (e.g. fisheries, hunting) has substantial effects on life expectancy and age at maturity. Although demographic rates of trees are impacted by recurrent harvest of plant organs (e.g. fruit, leaf, bark) known as non‐timber forest products, the effect of such harvesting on life‐history traits is less explored. Here, we investigate how different strategies of foliage and bark harvest by local people affect life expectancy and age at maturity of Khaya senegalensis across two climatic regions in West Africa. We compare elasticities of life expectancy to perturbation of vital rates to the elasticities of population growth rate, emphasizing how the two kinds of elasticity address distinct biological issues and management goals. Life expectancy was shorter and reproduction delayed in the dry than in the moist region, indicating a cost of drought to life‐history traits. Harvesting at constant rates only affects (increased) life expectancy in the moist region and (reduced) age at first reproduction in the dry region. Models in which harvest intensity varies stochastically over time show results similar to those with constant harvesting rate. However, there is an interactive effect of harvest on life‐history traits between regions. Increasing harvesting pressure accelerates maturity and reduces life expectancy in the dry region but delays reproduction and increases life expectancy in the moist region. This indicates that stochasticity magnifies the effect of harvesting on life‐history traits. With the notable exception of heavily harvested populations in the moist region, life expectancy is more elastic to survival of early rather than late life stages. This pattern contrasts with the elasticity of population growth rate; the latter is more elastic to survival of late rather than early life stages. Sy nthesis . Our results suggest that plant harvesting can affect life‐history traits but in different ways across an environmental gradient. Failure to account for stochasticity in harvesting rate can mask some of these effects. Our results also indicate that processes driving plant life expectancy, at least for long‐lived species, may differ from those driving population dynamics. Abstract : Our results suggest that plant harvesting can affect life‐history traits but in different ways across an environmental gradient. Failure to account for stochasticity in harvesting rate can mask some of these effects. Our results also indicate that processes driving plant life expectancy, at least for long‐lived species, may differ from those driving population dynamics.